Disability payments continue to climb: "Tell us what you see, not what you think," CPP tells MDs - Baer, N (1997)
Growing concern about the sustainability of the Canada Pension Plan has led to a closer look at the disability benefits it provides. The federal auditor general reported recently that the number of recipients has almost doubled in the past 10 years, and disability payments have more than tripled, to $3 billion annually. This article looks at the role physicians play in determining whether an applicant is disabled.